Improving Students’ English Writing Skill Through Storytelling Technique - syamsul Rizal (Tarbawi, 2021)
This research is designed to improve the students’ writing skill in English through storytelling technique. This research involved 42 second semester students of PAI Program of Tarbiyah Faculty of IAI Hamzanwadi NW Pancor. The objective of the research is to apply the procedure of storytelling technique to improve the students’ writing skill. The method applied in this research was a classroom action research. The data of the research were gathered through observation checklist, questionnaire, and writing test. The finding showed that storytelling technique was successful in improving students’ writing skill. The improvement could be seen from the improvement of students’ scores in writing test. Besides, the finding also showed that storytelling technique can improve the students’ involvement and enhance their interest in learning English, especially in writing.